Assessing the Istislahiah Method in Islamic law: Study of The Utilization of Science in Ushul Fiqh in The Context of Indonesian Fiqh - Silsilu Durrotil Bahiyah (Indonesian Journal of Law and Islamic Law (IJLIL), 2024)
Traditional Islamic law is often seen as being based on textual sources, such as the Qur'an and Sunnah. However, a closer look reveals that scholars have a long history of incorporating scientific advancements into legal reasoning. This paper explores the istislahiah method, which uses scientific knowledge to formulate Islamic legal rulings in the context of contemporary Indonesia. The paper begins by examining the concept and authority of the istislahiah method. It traces its historical roots to the early days of Islam, and discusses the theoretical underpinnings of the method. The paper also explores the debates surrounding the validity of istislahiah in Islamic legal discourse. The paper then turns to the practical application of istislahiah. It analyzes how scientific knowledge can be integrated into legal reasoning to address pressing social issues faced by Indonesia. The paper provides examples of how istislahiah has been used to address issues such as public health, environmental protection, and gender equality. Finally, the paper explores how the istislahiah method can enhance Islamic law for the future. It argues that istislahiah can help to bridge the gap between traditional Islamic legal principles and the evolving realities of the modern world. By demonstrating the compatibility of science and Islamic law, istislahiah can pave the way for a more nuanced and adaptable approach to legal decision-making in Indonesia. This study offers a fresh perspective on the potential of the istislahiah method to address the challenges of the modern world. By demonstrating how scientific knowledge can be used to formulate Islamic legal rulings, this research paves the way for a more dynamic and contextually relevant Islamic legal framework for Indonesia.